Budget Analysis as a Tool to Monitor Economic and Social Rights: Where the Rubber of International Commitment Meets the Road of Government Policy. (27th February 2017) - Manion, Megan; Ralston, Robert; Matthews, Thandi; Allen, Ian
Abstract: This policy and practice note investigates budget analysis as a potential method for human rights practitioners to adopt and implement in their ongoing work. It uses expert interviews, detailed reviews of prior budget analyses, and academic literature to identify the strengths and weaknesses of budget analysis as a method. Budget analysis is a powerful tool for human rights activists. Budgets represent a key piece of evidence for practitioners to hold governments accountable to their obligations to increasingly and effectively generate, allocate, and expend resources for economic and social rights-related programmes. However, there are important issues to consider before conducting a budget analysis, including available expertise and institutional interest in investment, the ability to monitor state allocation over time, and how to work closely with governments. There are also clear limitations to budget analysis as a method, including lack of credible and accessible data, its effectiveness as a monitoring mechanism, and how it can further entrench the assumption that economic and social rights are not on an equal footing with civil and political rights. Despite these issues and limitations, budget analysis should be considered an important, and viable, method for practitioners to consider using in their advocacy efforts.